Greed Supports Economic Growth But Might Make Us More Miserable - Nissim, Ben David; Tchai, Tavor; Zvi, Winer (Scientific Research, 2016)
Most economists, who refer to utility as representing wellbeing, do so under the assumption that utility increases with consumption. In contrast, lately researchers have found evidence that individuals' wellbeing is by far a more complicated matter than to be represented solely by their consumption choices. Adopting a broader approach to human wellbeing, we have modified the traditional theory to include income aspirations. Following this new line of thinking, this paper assumes that individuals seek to minimize the gap between their consumption aspirations and their consumption desires, namely minimizing their frustration. We present an overlapping generation model and assume that desires increase with current and lag consumption. Our theoretical results show that in an economy with agents minimizing frustration, as greed increases, the steady state level of capital might be higher while people would certainly be more miserable.
Keywords: Frustration; Desires; Equilibrium; Two Period Consumption Model